Q-switched and mode-locked lasers in 1.55 and 2.0 μm using selected 2d materials as saturable absorber / Rizal Ramli - Rizal , Ramli (2023)
Ultrafast pulse laser generation in photonics has gained significant interest in fundamental science and various industries, such as telecommunications, sensing, industrial processing and medicine. Passively Q-switched and mode-locked fiber lasers are recent developments that produce efficient pulse lasers by incorporating gain medium, saturable absorber (SA) materials and SA hosts. In this research, tapered fibers were fabricated and characterised using the flame-brushing technique, with a tapered waist of approximately 7 μm. Passively Q-switched laser and mode-locked lasers were generated in the laser cavities. Due to the emergence of novel SA materials, the research focused on the nonlinear properties of gain medium such as erbium- and thulium-doped fiber lasers; SA materials, such as GO, Ta2AlC MAX Phase and Nb2C MXene; and SA hosts, such as PVA films and tapered fibers, to generate pulse fiber lasers. The results of this work demonstrated that the modulation depth ranged from 1.91 to 41.05%, indicating efficient SA material absorption on the SA hosts. Using PVA film, passively Q-switched fiber lasers generated had a center wavelength ranging from around 1556.20 to 1967.27 nm, repetition rates around 19.83 to 68.52 kHz, pulse widths ranging from around 11.60 to 1.14 μs, signal-to-noise ratio (SNR) values from 23.44 to 74.00 dB and maximum pulse energy ranging from 5.41 to 31.28 nJ. Using tapered fiber, passively mode-locked fiber lasers generated had a center wavelength ranging from around 1555.2 to 1948.3 nm, repetition rates around 9.35 to 16.49 MHz, pulse widths ranging from around 0.63 to 1.68 ps and SNR values ranging from around 52.00 to 74.46 dB. It is noteworthy that tapered fiber and Nb2C MXene produced superior pulse fiber laser performance compared to other SA devices, indicating that these components may provide novel inroads to future research approaches in nonlinear cavities for generating ultrafast pulse fiber lasers. In conclusion, the findings demonstrate excellent performance of selected SA materials covered onto tapered fiber, which would offer opportunities to further explore the fundamental science of photonics and pulse laser for the future development of photonic devices for industry, medicine and the environment.